From Wealth to Power: The Unusual Origins of America's World Role by Fareed Zakaria. Princeton: Princeton University Press, 1998, 199 pp. (American Journal of Islam and Society, 2000)
From Wealth to Power is a study in the social and historical dynamics contributingto the rise and fall of essential actors in the international system. Itattempts to join history with social sciences theory in order to shed light onbroad theoretical topics in world politics, such as the rise of new great powers.In so doing it seeks to add to the body of scholarship that combined the studyof state structure with traditional international relations theory. The particularfocus is on the expansive rise of the United States, not only to world prominence,but also as a modem state. American foreign policy during the period1865-1908 is examined in light of changes in the state structure along the fourmajor variables- scope, autonomy, coherence, and capacity (p. 40)- touchingupon that country's domestic and administrative development.The first of the six chapters of the book poses the main questions that Zakariaattempts to address: ''What turns rich nations into 'great powers'?'' "Why, as states grow increasingly wealthy, do they build large annies, entangle themselvesin politics beyond their borders, and seek international influence?""What factors speed or retard the translation of material resources into politicalinterests?" (p. 3) and finally, "Under what conditions do states expand theirpolitical interests abroad?" (p. 18). Such questions visualize, on the one hand,a strong and direct correlation between great powers' economic rise and falland their growth or decline. Anomalies, on the other hand, are explained as a"Dutch disease," or the malady that does not allow "a nation of unequalledindividual prosperity and commercial prowess from remaining a state of greatinfluence and power" (pp. 4-5). The latter, Zakaria claims, was an Americanaffliction during the second half of the nineteenth century. This was particularlytrue during the relatively long period of nonexpansion and isolation followingthe Civil War (1860--64). Despite a tremendous increase in wealth, productivity,and power, it was not until the 1890s that the US began expandingagain. Zakaria considers this to be an aberration, reflecting a "highly unusualgap between power and interests" that lasted for some thirty years (p. 5). Anexplanation, according to him, would not only require a full historical account,but also "first-cut theories" which clarify national behavior (p. 8) ...